Abortus dalam Perspektif Hukum Islam dan Hukum Positif - Rasyidin Imran (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Abortion is an act of terminating a pregnancy by aborting or removes the fetus from the womb. Beside, to eliminating the life right of the fetus in the womb, abortion compromises the safety of mothers who conceived and gradually will affect the lifestyles of the people are governed by cultural and religious norms. Because of these harmful actions, so as specify whether abortion is legal or it may not, have to consider the three parties. The act of abortion is not always bad. There are certain conditions that make the act of abortion can be tolerated and allowed. These conditions such as contraceptive failure, endangering the safety of the womb when the mother passed on, or because of the demands of one's job.